2022
DOI: 10.1007/s10147-022-02196-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of fistula occurrence in patients with cervical cancer treated with bevacizumab: data from real-world clinical practice

Abstract: Background This study aimed to determine the incidence of pelvic fistulas in cervical cancer patients treated with bevacizumab in Japanese clinical practice. Methods A post-marketing surveillance (PMS) study was conducted between June 2016 and February 2018 to survey physicians who treated advanced or recurrent cervical cancer patients with bevacizumab (according to the product label). The clinical/treatment status of patients with pelvic fistulas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This outcome was similar to that of the CECILIA study (11.3%) [ 16 ] and a multicenter study in the Kinki district of Japan (11.2%) [ 19 ]. A medical history of pelvic radiotherapy was considered a risk factor for fistula and intestinal perforation, as previously reported [ 2 4 16 19 20 ]. These studies reported that the rate of fistula formation or intestinal perforation in previously irradiated patients was 84%–100%.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome was similar to that of the CECILIA study (11.3%) [ 16 ] and a multicenter study in the Kinki district of Japan (11.2%) [ 19 ]. A medical history of pelvic radiotherapy was considered a risk factor for fistula and intestinal perforation, as previously reported [ 2 4 16 19 20 ]. These studies reported that the rate of fistula formation or intestinal perforation in previously irradiated patients was 84%–100%.…”
Section: Discussionmentioning
confidence: 99%